AB0801 Osteoporosis Frequency and The Association of Rank, Rankl, Osteoprotegerin Gene Polymorphisms with Osteoporosis in Gout Patients. (15th July 2016) - Karatay, C.C.; Balkarli, A.; Elmas, L.; Can, B.; Tepeli, E.; Cobankara, V.
Abstract : Background: Gout is a disease characterized by acute arthritis as a result of increased serum uric acid concentration and deposition of monosodium urate crystals into tissues. In recent times the significant role of RANK- RANKL- OPG network in bone remodeling and osteoclastogenesis was proven. In patients with osteoporosis and in rheumatoid arthritis patients, genetic variations in the genes encoding RANK, RANKL and OPG was investigated and conflicting results were obtained. Also the role of these genes in the pathogenesis of psoriasis, psoriatic arthritis and ankylosing spondylitis has been researched. There is not any study that evaluates RANK, RANKL, Osteoprotegerin gene polymorphisms and their association with the susceptibility to osteoporosis in gout patients. To the best of our knowledge, this is the first study to investigate this subject. Methods: 69 gout patients, 50 RA patients and 51 healthy controls were recruited for this study. BMD of lumbar spine and femoral sites were measured using DEXA. After acquisition of the BMD T- score, the patients and controls divided into normal, osteopenic and osteoporotic groups according to WHO criteria. We studied 7 SNP in the genes of RANK gene (2 SNP: rs1805034, rs35211496), OPG gene (2 SNP: rs3102735, rs 2073618) and RANKL gene (3 SNP: rs9533156, rs1054016, rs2277438) using real time PCR. Results: There was no significant difference for BMD scores between three groups. The 7 SNP genotypes showed no significant difference between three groups. The 7 SNP allel frequencies showed no significant difference between three groups. Gout patients with rs1805034 wild genotype had lower incidence of osteoporosis at the femoral sites. Gout patients with rs1805034 heterozygous genotype had higher incidence of normal BMD scores at the femoral sites than other gout patients. Controls with rs2277238 wild genotype, had lower incidence of osteoporosis and those with mutant genotype had higher incidence of osteoporosis at any sites than other controls. Controls with normal BMD at lumbar spine, frequency of rs35211496 wild genotype was higher than other controls. Conclusions: As a result it is seen that the C allel of the RANK SNP rs1805034 is protective against osteoporosis at femoral site in gout patients. The A allel of the RANKL SNP rs2277438 is protective against osteoporosis at either femoral sites or lumbar spine in healthy people. BMD in patients with Gout, RA and healthy population unexpectedly is not different from each other which may be related to low number of cases. Genotype distribution and genetic diversity varies between ethnic groups. There is a need for more studies with larger patient populations to explain the subject. Disclosure of Interest: None declared